Pengaruh Service Guarantee dan Perceived Quality Terhadap Satisfaction - Fadillah Adelia Larsitha; Sri Vandayuli Riorini; Alfi Mazzida; Azzahra Iansfri (Cattleya Darmaya Fortuna, 2025)
The purpose of this study is to explain the influence of service assurance and perceived quality on satisfaction in e-commerce in Indonesia. Where technological developments, especially the internet, have caused changes in Indonesian consumer purchasing habits, especially those related to e-commerce. Despite the growing popularity of online shopping, companies often face challenges in service delivery, such as late deliveries and misleading advertisements. The method used in this research is hypothesis testing with a cross-sectional approach. This study involves individual e-commerce users as the unit of analysis and uses a 5-point Likert scale to measure the variables studied: service guarantee, perceived quality, and satisfaction. Instrument testing in this study was carried out with validity and reliability tests involving 125 respondents whose results were proven valid and reliable so that hypothesis testing could be carried out. The results showed that there is a positive influence between service guarantee on satisfaction and perceived quality. This suggests that effective implementation of service guarantee can improve perceived service quality and in turn increase consumer satisfaction on e-commerce platforms.